Historiografi Masuknya Islam di Palembang dan Kaitannya dengan Perkembangan Kerajaan Sriwijaya - Astapala, Sultan Gholand (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The arrival of Islam in Palembang occurred in the 7th century, although some believe it occurred between the 13th and 16th centuries AD. This study aims to provide comprehensive information about the history of Islam's arrival in one of the oldest cities, Palembang, and its relationship to the development of the Srivijaya Empire. This study uses a historical method. The steps taken in this study are: first, heuristics, or the source collection stage; second, verification, where the collected data is tested for authenticity; third, interpretation, which involves interpreting or analyzing historical data and facts; and third, historiography, the writing of history based on the interpretations. The conclusion of this study is that Islam entered the Palembang area in the 7th century. Based on Arab theory, Islam was introduced by Arab traders. This is evidenced by several relics found in Palembang. The Islam brought by these traders was well-received and protected by the Sriwijaya rulers, who practiced Buddhism earnestly and prioritized interfaith and ethnic harmony. Even though Islam had entered Palembang since the 7th century AD, its spread was not fast because the official religion of the ruler at that time was Buddhism